Programming for peace computer-aided methods for international conflict resolution and prevention (Advances in group decision and negotiation ;, 2006)
Sadly enough, war, conflicts and terrorism appear to stay with us in the 21st century. But what is our outlook on new methods for preventing and ending them? Present-day hard- and software enables the development of large crisis, conflict, and conflict management databases with many variables, sometimes with automated updates, statistical analyses of a high complexity, elaborate simulation models, and even interactive uses of these databases. In this book, these methods are presented, further developed, and applied in relation to the main issue: the resolution and prevention of intra- and international conflicts. Conflicts are a worldwide phenomenon. Therefore, internationally leading researchers from the USA, Austria, Canada, Germany, New Zealand and Switzerland have contributed. This book is for students and scientists in international relations and political sciences, and decision makers or their advisers in national and international bodies, both governmental and non-governmental. I-- I - conflict resolution by democracies and dictatorships: are democracies better in resolving conflicts? -- trade liberalization and political instability in developing countries -- computer assisted early warning – the fast example -- country indicators for foreign policy developing an indicators-based user friendly risk assessment and early warning capability -- the confman.2002 data set developing cases and indices of conflict management to predict conflict resolution -- ii -- ii -- events, patterns, and analysis forecasting international conflict in the twenty-first century -- forecasting conflict in the balkans using hidden markov models -- neural computation for international conflict management -- modeling international negotiation statistical and machine learning approaches -- machine learning methods for better understanding, resolving, and preventing international conflicts -- iii -- iii -- new methods for conflict data -- information, power, and war -- modeling effects of emotion and personality on political decision-making -- peacemaker 2020 a system for global conflict analysis and resolution; a work of fiction and a research challenge.